On pairwise nearly Lindelof bitopological spaces - Salleh, Zabidin; Kilicman, Adem (Pushpa Publishing House, 2013)
We shall introduce and study the pairwise nearly Lindelöf bitopological spaces and obtain some results. Moreover, we study the pairwise nearly Lindelöf subspaces and subsets and investigate some of their characterizations. We also show that the pairwise nearly Lindelöf space is not a hereditary property. Some examples will be considered in order to establish some of their relationships. Finally, certain conditions on which a bitopology reduced to a single topology are investigated.